Functions of Endothelial Cilia in the Regulation of Vascular Barriers - Ma, Nan; Zhou, Jun (Frontiers in Cell and Developmental Biology, 2020)
The vascular barrier between blood and tissues is a highly selective structure that is essential to maintain tissue homeostasis, and defects in the vascular barrier can lead to a variety of cardiovascular diseases. The maintenance of vascular barriers is largely dependent on endothelial cells, but the precise mechanisms remain elusive. Recent studies reveal that primary cilia, microtubule-based structures that protrude from the surface of endothelial cells, plays a critical role in the regulation of vascular barriers. Herein, we discuss recent advances on ciliary functions in the vascular barrier and suggest that ciliary signaling pathways might be targeted to modulate the vascular barrier.